Identifikasi Perkembangan Kognitif Anak Usia 4-5 Tahun di Kecamatan Seteluk - Dwi Cici Maylani; I Nyoman Suarta; Gunawan Gunawan (Indonesian Publication Center, 2022)
This study aims to determine the cognitive development of children aged 4-5 years in Seteluk District. This study uses a type of survey research. With the study population all children aged 4-5 years in Seteluk District, totaling 384 children and the sampling technique using a stratified proportional random sampling technique, a sample of 80 children found in 5 schools. The data collection method used was observation and interview techniques, while the data analysis technique used was quantitative descriptive analysis technique. As for the results of the study, it showed that the cognitive development of children aged 4-5 years in the aspects of learning and problem solving in Seteluk District based on an average yield of 61.00%. The aspect of logical thinking reaches 58.50% and the aspect of symbolic thinking reaches 60.57%. Therefore it can be concluded that of the three aspects of cognitive development, the dominant ones developing are the aspects of learning and problem solving.